Direct immunofluorescence (DIF) versus immunohistochemical (IHC) staining of complements and immunoglobulins (Ig) in pemphigus group - Deepika Rana; Nita Khurana; Shramana Mandal; Bijay Laxmi Sahoo (Indian Journal of Pathology and Microbiology)
Introduction: Pemphigus is a group of bullous disorders of the skin characterized by the formation of autoantibodies present in the intercellular junction of the epidermis. Diagnosis is made by clinical, histopathological examination, and DIF. As DIF needs frozen sections, fluorescent tagged antibodies, UV light microscope for examination, and trained personnel, its non-availability makes a definitive diagnosis challenging. Aims and Objectives: To evaluate the utility of IHC staining of complements and Ig in cases of Pemphigus. Materials and Methods: Twenty-six diagnosed cases of Pemphigus were stained by Peroxidase immunohistochemical method using monoclonal antibody to IgG, IgA, IgM, IgG4, C3, C4 d with DAB as chromogen. Pemphigus cases include twenty of pemphigus vulgaris (PV), four cases of pemphigus foliaceous (PF), and two of pemphigus vegetans (Pveg). Positivity was defined as the deposition of Ig and complements as distinct, continuous brown staining of keratinocytes at intercellular junctions. Result: On IHC total of 20 PV 17 showed positivity (85%) for IgG, 11 (55%) C4d, 19 (95%) C3d, and 16 (80%) IgG4 deposits at the intercellular junction of the epidermis. All cases of PF showed a deposit of IgG, with three (75%) cases for IgG4, C3d, and C4d. Both cases of Pveg showed positivity for IgG and C4d while one case was negative for IgG4 and C3d. The overall IgG, C3, IgG4, and C4d expression for pemphigus was seen in 88%, 88%, 76.9%, and 61.5% of cases. The relation between these markers, combination of IgG and C3, was best related to each other (P value = 0.80). The sensitivities for IgG, IgG4, and C3 were 77.8%%, 73%, and 73% resp. Conclusion: We conclude that IHC is a useful tool in the diagnosis of PV with the highest sensitivity of IgG and C3d. The combination of IgG and C3d could replace the DIF in almost all of our cases, so IHC on FFPE sections be used as an alternative method to DIF.